Video teaching leads to improved attitudes towards obesity: a randomized study with 949 participants - Nickel, Felix; Benner, Laura; Schüler, Svenja; Ottawa, Gregor; Krug, Katja; Fischer, Lars (Obesity surgery, 2019)
BackgroundObesity is a rising social and economic burden. Patients with obesity often suffer from stigmatization and discrimination. Underrecognition of obesity as a disease could be a contributing factor. The present study aimed to compare attitudes towards obesity with other chronic diseases and to evaluate the recognition of need of professional treatment.MethodsNine hundred and forty-nine participants (subgroups: general population, patients with obesity, nurses in training, nurses, medical students, physicians) were randomized to video teaching on obesity and control. Questionnaires on the burden and influence of obesity on daily life compared to other chronic diseases and the fat phobia scale (FPS) were answered.ResultsBurden of obesity was rated low (4.2 ± 1.3; rank 9 of 11) compared to other diseases. Bowel cancer (5.5 ± 0.9) had the highest and caries the lowest (2.7 ± 1.4) estimated impact. Females (p = 0.011) and older people (p < 0.001) rated burden of obesity high whereas general population (p < 0.001) and control (p < 0.001) rated it low. Females (p = 0.001) and people with higher BMI (p = 0.004) rated the influence of obesity on daily life high; the general population (p < 0.001; reference physicians) and the control group (p < 0.001) rated it low. FPS was lowest in patients with obesity (3.2 ± 0.7) and highest in the general population (3.6 ± 0.4) and medical students (3.6 ± 0.5; p < 0.001; compared to physicians).ConclusionsObesity is underestimated as a disease compared to other chronic diseases and attitudes towards obesity are rather negative in comparison. Video teaching showed positive effects so a focus in medical education and public campaigns should aim to improve prevention and treatment of obesity.